Hybrid Religious Engagement: Generation Z’s Negotiation of Faith Across Digital and Physical Spaces - Saputra, Dedi (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2025)
This article discusses the phenomenon of hybrid religious engagement among Generation Z students at the Riyadlatul Ulum Islamic Boarding School, Batanghari, East Lampung. Born and raised in the digital era, Gen Z students not only interact with traditional religious authorities in the Islamic boarding school environment, but also actively access, interpret, and distribute religious narratives from various digital platforms. This study aims to examine how students negotiate their religious beliefs, practices, and identities amidst the tension between Islamic boarding school traditions and digital religious populism. This study uses a qualitative approach with a case study method and data collection techniques in the form of in-depth interviews with six informants, male and female students. The results of the study indicate that the consumption patterns of digital content by students are selective, reflective, and adaptive. The tension between traditional authority (such as yellow books and kiai fatwas) and digital narratives (viral preaching, instant interpretation) gives rise to a complex dialectic, but at the same time encourages the construction of a new religious identity called